Gene knockout of glutathione reductase results in increased sensitivity to heavy metals in Acidithiobacillus caldus - Shi, Yuping; Wu, Wei; Yang, Yinghui; Liu, Xiao; Lin, Jianqiang; Liu, Xiangmei; Lin, Jianqun; Pang, Xin (Frontiers in Microbiology, 2023)
Acidithiobacillus caldus plays an important role in bioleaching of low grade metal ore. It can promote the release of heavy metals in mining-associated habitats and survive in high concentrations of heavy metals. Functions of glutathione reductase (GR) in cell defense against reactive oxygen species caused by heavy metals have been elucidated in some eukaryotic cells and bacteria, however, no information is available in A. caldus.Here, a putative gr gene F0726_RS04210 was detected in the genome of A. caldus MTH-04. The purified recombinant protein of F0726_RS04210 showed remarkable GR activity at optimal pH 7.0 and 30 ℃ by in vitro assay. The evolutionary relationship of GR from A. caldus MTH-04 was close to that from Escherichia coli K12. Gene knockout or overexpression of gr in A. caldus did not affect growth rate on S 0 medium obviously, suggesting that GR did not play a key role in the activation of sulfur. Deletion of gr resulted in increased sensitivity to heavy metals (Cu 2+ and Zn 2+ ) in A. caldus, and the gr overexpression strain showed enhanced tolerance to heavy metals. Furthermore, transcription analysis also revealed the strong correlations between GR and the antioxidant pathway. Above results suggest that GR can play an important role in heavy metal tolerance in A. caldus.